KONTRIBUSI MANAJEMEN BERBASIS SEKOLAH (MBS) DAN KEPUASAN KERJA TERHADAP PELAKSANAAN KINERJA GURU DI SD MUHAMMADIYAH MARTAPURA - Latifah Latifah; Noor Fazariah Handayani (Jurnal Terapung : Ilmu - Ilmu Sosial, 2022)
In this study, the analysis process carried out on the data that has been collected has been interpreted on the results of the process, so some conclusions are drawn as follows: Generally, the implementation of SBM in SD Muhammadiyah Martapura is classified as good, the level of teacher job satisfaction, especially after SBM is implemented, turns out to be quite high. , School performance which is manifested in the form of school accreditation scores is generally classified as good, There is a significant contribution from the implementation of SBM to the level of teacher job satisfaction, There is also a significant contribution from teacher job satisfaction to school performance results, There is a significant contribution from the implementation of SBM and teacher job satisfaction on the performance of SD Muhammadiyah Martapura. All hypotheses proposed in this study were significantly accepted.Keywords: Contribution, school-based management, job satisfaction.